Research on the Efficiency of Higher Education Resource Allocation in China’s Five Major Economic Circles - Tang, Miaomiao; Wang, Jingxian; Zeng, Zhen (Journal of Educational Research and Policies, 2025)
China’s Five Major Economic Circles serve as engines of national economic growth. Studying the efficiency of higher education resource allocation in these regions holds significant importance for promoting China’s high-quality economic development. This study employs Data Envelopment Analysis (DEA) to analyze the efficiency of higher education resource allocation and its regional disparities within China’s Five Major Economic Circles from 2018 to 2022.The results indicate that the overall efficiency of higher education resource allocation in the Five Major Economic Circles remains relatively low, with pronounced regional disparities. While technological progress across the circles generally maintained a high level and scale efficiency achieved dynamic balance, the decline in pure technical efficiency emerged as the primary cause of the low resource allocation efficiency. Based on these findings, this study proposes several recommendations: establishing a rational and scientific investment system for higher education resources; fully leveraging the spatial spillover effects of higher education; implementing macro-level management system reforms and innovations within universities; and enhancing the external coordination and integration of advanced scientific and technological resources. These measures aim to improve the efficiency of higher education resource allocation in the Five Major Economic Circles and further propel China’s economic development.